Delayed reproductive development in pubertal male rats exposed to the hypolipemiant agent rosuvastatin since prepuberty - Araujo Leite, Gabriel Adan [UNESP]; Rosa, Josiane de Lima [UNESP]; Sanabria, Marciana [UNESP]; Cavariani, Marilia Martins [UNESP]; Anselmo Franci, Janete Aparecida; Felipe Pinheiro, Patricia Fernanda [UNESP]; Kempinas, Wilma De Grava [UNESP] (Elsevier B.V., 2014)
Dyslipidemias are frequently found in children due to obesity, bad eating habits and the lack of physical exercises. Rosuvastatin acts as an HMG-CoA reductase inhibitor, decreasing total cholesterol and triglycerides. This study aimed to investigate initial sexual development and morphological aspect of the testis and epididymis in juvenile rats exposed to rosuvastatin since pre-puberty. Three groups were formed with newly weaned rats: control, whose rats received saline solution 0.9%, rosuvastatin at doses of 3 or 10 mg/kg daily by gavage, since post-natal day 21 until puberty onset. In the rosuvastatin-treated groups, the results demonstrated a trend toward a decrease in testosterone concentration, but below the significance level, as well as delays in both the age of puberty onset and in epididymal development. There were also testicular alterations that might be related to delayed puberty and decrease of serum testosterone. In conclusion, rosuvastatin administration to juvenile rats not only delayed puberty onset and epididymal development, but also impaired testicular and epididymal morphology. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Male reproduction; Puberty; Rosuvastatin; Androgen receptors; Epididymis